Comics studies in the Nordic countries – field or discipline?. Issue 2 (2nd April 2016) - Strömberg, Fredrik
Abstract : The last few years have seen a flurry of academic activities on comics in the Nordic countries. But are we on the verge of establishing an independent field or a discipline of comics studies, or both? And if so, is this desirable? On an international level, comics studies have for some time been an intellectual field and can now be said to be on a pre-paradigmatic level as a discipline. In the Nordic countries, the field of comics studies has grown rapidly the last few years, but it is still very much dispersed, with researchers working at different departments and within a number of disciplines. There are tendencies towards a maturing into a more cohesive field, but this is a recent development. The establishing of a comics studies discipline, though keeping an open 'rural mode' of knowledge production to prevent a loss of the positive aspects of interdisciplinary research, would facilitate the possibilities for professors' seats, journals, specific grants, recurring conferences and research libraries – and thus a more rapid growth of comics studies.